Effectiveness of preoperative stretchings on postoperative shoulder function in patients undergoing mastectomy - Tehreem Fatima; Aiman Shakoor; Mahnoor Ilyas; Maryam Safdar; Sidra Majeed (Journal of the Pakistan Medical Association, 2022)
Objective: To analyze the effects of pre-operative stretchings of shoulder muscles on post-operative shoulder function in patients undergoing mastectomy. Method: Randomized controlled trial was conducted on mastectomy patients for four months. Total 30 patients were taken from Allied hospital, Madinah Teaching Hospital (MTH), District Head Quarter (DHQ) Hospital, Faisalabad through convenient sampling and randomly allocated in treatment and control group. The data was collected by using Numeric Pain Rating Scale (NPRS), Universal goniometer & Groningen Activity Restriction Scale (GARS) at post-op day1 and day3. Those patients who met the study criteria and gave consent were included in the study. Treatment group received static stretching with ROMs and control group received routine care as followed pre-operatively in setting. Results: Treatment group showed statistically significant difference (p<0.05) in pain, Range Of Motion (ROMs) and GARS score for Activities of Daily Living (ADLs) from control group. Treatment group showed decreased pain and improved shoulder flexion and abduction ROMs at post op day 1st and 3rd while treatment group showed non-significant difference (p>0.05) in external rotation and GARS score at post op day 1st but Significant difference (p<0.05) at post op day 3rd was observed. Conclusion: Pre-operative stretching of shoulder muscles are proved to be safe and effective in reducing post operative pain and functional restriction in patients undergoing mastectomy. Keywords: Pre-operative stretching, Stretching of shoulder muscles, Post-op shoulder function, Mastectomy. Continue